Administration of pilocarpine by microneedle patch as a novel method for cystic fibrosis sweat testing. Issue 3 (3rd April 2021) - Li, Song; Hart, Kelsey; Norton, Natalie; Ryan, Clare A.; Guglani, Lokesh; Prausnitz, Mark R.
Abstract: The sweat test is the gold standard for the diagnosis of cystic fibrosis (CF). The test utilizes iontophoresis to administer pilocarpine to the skin to induce sweating for measurement of chloride concentration in sweat. However, the sweat test procedure needs to be conducted in an accredited lab with dedicated instrumentation, and it can lead to inadequate sweat samples being collected in newborn babies and young children due to variable sweat production with pilocarpine iontophoresis. We tested the feasibility of using microneedle (MN) patches as an alternative to iontophoresis to administer pilocarpine to induce sweating. Pilocarpine‐loaded MN patches were developed. Both MN patches and iontophoresis were applied on horses to induce sweating. The sweat was collected to compare the sweat volume and chloride concentration. The patches contained an array of 100 MNs measuring 600 μm long that were made of water‐soluble materials encapsulating pilocarpine nitrate. When manually pressed to the skin, the MN patches delivered >0.5 mg/cm 2 pilocarpine, which was double that administered by iontophoresis. When administered to horses, MN patches generated the same volume of sweat when normalized to drug dose and more sweat when normalized to skin area compared to iontophoresis using a commercial device. Moreover, both MN patches and iontophoresis generated sweat with comparable chloride concentration. These results suggest that administration of pilocarpine by MN patches may provide a simpler and more‐accessible alternative to iontophoresis for performing a sweat test for the diagnosis of CF.